Pengaruh kepercayaan diri dan minat terhadap prestasi belajar matematika siswa madrasah aliyah swasta di Kabupaten Pandeglang - Ruri Rantau; Syamsuri Syamsuri; Hepsi Nindiasari (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
Abstract: This study aims to describe the effect of self-confidence and interest on student achievement. This research is a survey research. secondary data is taken from mid-semester assessment and end-semester assessment, class X students, academic year 2020/2021. The population of this research is the students of private Madrasah Aliyah in Pandeglang Regency, zone three working group of MAN 3 Pandeglang consisting of nine Private Madrasah Aliyah. Sampling using the Slovin formula and using cluster random sampling technique, based on this technique, 191 samples were obtained. The data collection technique used a questionnaire of 18 statements, the data that had been collected was analyzed using Partial Least Squares Structural Equation Modeling (PLS–SEM). The results of the study revealed that: (1) interest in learning and self-confidence together can explain students' learning achievement by 24.8% (2) There is an influence of self-confidence and interest on students' mathematics learning achievement, namely 0.460 (t = 8.662, p < 0.05) and 0.206 (t = 3.721, p<0.05).